A Concept Mapping Study of Physicians’ Perceptions of Factors Influencing Management and Control of Hypertension in Sub-Saharan Africa - Juliet Iwelunmor; Sarah Blackstone; Joyce Gyamfi; Collins Airhihenbuwa; Jacob Plange-Rhule; Bamidele Tayo; Richard Adanu; Gbenga Ogedegbe (International Journal of Hypertension)
Hypertension, once a rare problem in Sub-Saharan Africa (SSA), is predicted to be a major cause of death by 2020 with mortality rates as high as 75%. However, comprehensive knowledge of provider-level factors that influence optimal management is limited. The objective of the current study was to discover physicians’ perceptions of factors influencing optimal management and control of hypertension in SSA. Twelve physicians attending the Cardiovascular Research Training (CaRT) Institute at the University of Ghana, College of Health Sciences, were invited to complete a concept mapping process that included brainstorming the factors influencing optimal management and control of hypertension in patients, sorting and organizing the factors into similar domains, and rating the importance and feasibility of efforts to address these factors. The highest ranked important and feasible factors include helping patients accept their condition and availability of adequate equipment to enable the provision of needed care. The findings suggest that patient self-efficacy and support, physician-related factors, policy factors, and economic factors are important aspects that must be addressed to achieve optimal hypertension management. Given the work demands identified by physicians, future research should investigate cost-effective strategies of shifting physician responsibilities to well-trained no-physician clinicians in order to improve hypertension management.